Conservation and conflict in the Democratic Republic of Congo: The impacts of warfare, mining, and protected areas on deforestation. (November 2015) - Butsic, Van; Baumann, Matthias; Shortland, Anja; Walker, Sarah; Kuemmerle, Tobias
Abstract: Tropical forests provide critical ecosystem services worldwide. Nonetheless, ongoing agricultural expansion, timber extraction, and mining continue to jeopardize important forest resources. In addition, many tropical forests reside in countries that have experienced violent conflict in recent decades, posing an additional, yet poorly understood threat. Conflict may decrease or increase deforestation depending on the relationship between conflict and other causes of land use change, such as mining expansion or protected area establishment. The Democratic Republic of Congo (DRC), home of the second largest tropical forest in the world, has experienced 20 years of violent conflict, resulting in the death of over 100, 000 combatants and up to 5 million civilians. Expanding mining concessions also threaten the DRC's forest, even though nearly 12% of it is under some form of protection. In this study, we used spatially-explicit data on conflict, mining, and protected areas, along with a host of control variables, to estimate the impacts of these factors on forest cover loss from 1990 to 2010. Through a panel instrumental variables approach we found that: i) conflict increased forest cover loss, ii) mining concessions increased forest cover loss, but in times of conflict this impact was lessened, and iii) protected areas reduced forest cover loss, even in high conflict regions. Our results thus suggest that policy interventions designed to reduce violent conflict may have the co-benefit of reducing deforestation, especially in areas with low mining potential. Likewise, protected areas can be effective even in times of war. Highlights: Conflict and mining increase forest loss. Conflict lessens forest loss in areas with high level of mining. Protected areas reduce forest loss, even during conflict.